Implementation of Character Education in Elementary Schools (A Case Study at SD Negeri Puspitek, South Tangerang) - Sutarman; Sofian; Kumar Saurav (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to provide an in-depth description of the implementation of character education at SD Negeri Puspitek, South Tangerang. Character education plays a crucial role in shaping students’ personalities from an early age, encompassing values such as honesty, responsibility, discipline, cooperation, and tolerance. This research employs a qualitative approach with a case study method. Data were collected through observations, in-depth interviews with the principal, teachers, and students, as well as documentation of school programs related to character reinforcement. The findings reveal that character education at SD Negeri Puspitek is implemented through integration into subject lessons, routine school activities, spontaneous activities, teacher modeling, and the development of a school-wide culture. Teachers play a vital role as role models in instilling character values in students. Additionally, the school organizes various extracurricular programs and flagship activities such as Friday Clean-Up, dhuha prayer habituation, and morning literacy sessions as platforms for character formation. Nevertheless, the study also identifies several challenges, including limited resources, diverse student backgrounds, and the lack of parental involvement in supporting character education at home. In conclusion, the implementation of character education at SD Negeri Puspitek has been carried out effectively and is integrated across various aspects of school life. However, achieving optimal outcomes requires stronger synergy among the school, teachers, students, and parents to continuously cultivate and reinforce character values.